الدور الوسيط لرضا العملاء في العلاقة بين التسويق الحسي ونية تكرار الزيارة: دراسة ميدانية على المطاعم بمحافظة المنوفية - عبدالواحد، يارا محمد محمد; سليمان، لمياء عبدالرحيم عبدالكريم Suleiman, Lamia Abdulrahim Abdulkarim (جامعة عين شمس - كلية التجارة, 2021)
يهدف هذا البحث إلى الكشف عن أثر أبعاد التسويق الحسي الخمسة (البصر، السمع، الشم، التذوق، اللمس) على كلا من رضا العملاء ونية تكرار بمطاعم محافظة المنوفية الخاضعة للبحث، بالإضافة إلى تحديد أثر رضا عملاء مطاعم محافظة المنوفية الخاضعة للبحث على نية تكرارهم الزيارة، وأخيرا قياس الدور الوسيط لرضا عملاء مطاعم محافظة المنوفية الخاضعة للبحث العلاقة بين التسويق الحسي بأبعاده الخمسة (البصر، السمع، الشم، التذوق، اللمس) ونية تكرارهم الزيارة، وتم التوصل إلى مجموعة من النتائج أهمها يوجد تأثير معنوي لأبعاد التسويق الحسي مجتمعة على كلا من رضا العملاء ونية تكرار الزيارة كلا على حدة، كما تم التوصل إلى زيادة تأثير كافة أبعاد التسويق الحسي مجتمعة على نية تكرار الزيارة وذلك عند توسيط رضا العملاء.
This research aims to detect the impact of the five sensory marketing dimensions (sight, hearing, smell, taste, touch) on both customer satisfaction and the intended frequency of restaurants in the province of Manofia subject to research, in addition to determining the impact of the satisfaction of customers of the restaurants of the province of Manofia subject to the subject of research, in addition to determining the impact of the satisfaction of customers of the restaurants of the province of Manofia subject to research, in addition to determining the impact of the satisfaction of customers of the restaurants of the province of Manofia subject to the subject of To look at the intention of repeating the visit, and finally measure the intermediate role of the satisfaction of the customers of the restaurants of The Province of Manofia subject to research the relationship between sensory marketing in its five dimensions (sight, hearing, smell, taste, touch) and the intention of repeating the visit, and a set of results were reached The most important is the moral impact of the dimensions of sensory marketing combined on both customer satisfaction and the intention to repeat the visit individually, as it was reached to increase the impact of all dimensions of sensory marketing combined on the intention of repeating the visit, when the customer satisfaction is mediated.
Keywords: المطاعم -- التسويق الحسي -- رضا العملاء -- نية تكرار الزيارة -- محافظة المنوفية -- مصر